The cultural activities cluster in Portugal: trends and perspectives - Costa,Pedro (2002)
The aim of this article is to evaluate briefly the importance of cultural activities in the Portuguese economy, identifying the main trends and opportunities for this cluster in todays world. The concept of "cultural industries" is discussed and the role of the cluster in the Portuguese economy and society is analysed, on the basis of empirical information, both statistical and qualitative. The territorial dimension of the organization of the cluster is strongly emphasized, with a comparative regional perspective being used to study the provision and consumption of these goods. Also explored is the relationship between the economic, cultural and institutional processes that are beyond the provision of these activities, and which are central to their comprehension.